IMPLEMENTATION OF THE C.50 ALGORITHM IN ASSESSING EMPLOYEE PERFORMANCE ON PT SMARTFREN TELECOM TBK - Purba, Windania; Caprio, Calvin Di; Sabrian, Muhammad Ryan (Sean Institute, 2022)
This study aims to create a model in measuring the performance of PT Smartfren Telecom employees which is measured based on several attributes such as performance targets, service orientation, integrity, discipline, cooperation and leadership. By using data mining data analysis methods, decision trees and the C.50 Algorithm, so that it can make a pattern of decisions that can be proposed as a basis for giving rewards and punishments for the performance of PT Smartfren employees. The population of the data is 30 respondents with 7 categories of leaders and 23 as employees. The results of this study are the C5.0 algorithm can process employee performance data into a decision tree and useful rules as input. The results obtained can be developed into a decision-making system so that it can be used to assist in determining employee performance decisions. In general, based on the evaluation results for staff data with training data as much as 23 data obtained an accuracy rate of 97%, where one of the factors that affect accuracy is that performance data does not meet the requirements which are still small, this can be increased by increasing the amount of training data related to the data